2021
DOI: 10.5194/soil-7-785-2021
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of <i>n</i>-alkanes from plant to soil: a review

Abstract: Abstract. Despite the importance of soil organic matter (SOM) in the global carbon cycle, there remain many open questions regarding its formation and preservation. The study of individual organic compound classes that make up SOM, such as lipid biomarkers including n-alkanes, can provide insight into the cycling of bulk SOM. While studies of lipid biomarkers, particularly n-alkanes, have increased in number in the past few decades, only a limited number have focused on the transformation of these compounds fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 110 publications
(186 reference statements)
0
17
0
Order By: Relevance
“…This may be due to the change of concentration in the process of long‐chain and short‐chain n‐alkanes transport, resulting in lower prediction accuracy of source contributions. Some studies have proposed that n‐alkanes can be degraded by soil microorganisms (De Pasquale et al, 2012; Schäfer et al, 2016; Thomas et al, 2021). The enrichment or depletion of sediment in the process of transport may also lead to a change in the concentration of n‐alkanes (Li et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the change of concentration in the process of long‐chain and short‐chain n‐alkanes transport, resulting in lower prediction accuracy of source contributions. Some studies have proposed that n‐alkanes can be degraded by soil microorganisms (De Pasquale et al, 2012; Schäfer et al, 2016; Thomas et al, 2021). The enrichment or depletion of sediment in the process of transport may also lead to a change in the concentration of n‐alkanes (Li et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…As organic molecules, biomarkers are subject to degradation processes during transport and deposition (e.g. Madureira et al ., 1997; Wakeham et al ., 1997; Thomas et al ., 2001). However, different classes of organic compounds have varying rates of degradation (Arndt et al ., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Fatty acids, and especially phospholipid fatty acids (PLFA) analysis have long been used to study soil microbial community structure and responses to various agricultural management. In studies with anthropogenic soils and or matrices that contain burnt (pyrolyzed) organic matter, however, it has been shown that alkanes distribution brings about detailed and complex view of sources and origin of soil organic matter (SOM), because of their higher hydrophobicity and stability to degradation, and also their use as a proxy to determine past vegetation environments (Atanassova et al, 2012;Eckmeier and Wiesenberg, 2009;Thomas et al, 2021).…”
Section: Introductionmentioning
confidence: 99%